Pandemic and Online Learning at Engineering Colleges - Ayuningrum, Erica Devi; Wihidayat, Endar Suprih; Liantoni, Febri (Universitas Sebelas Maret, 2023)
The Covid-19 pandemic has resulted in social restrictions being implemented in all sectors of life, including the scope of education. The closure of schools, higher education, and other educational institutions resulted in face-to-face learning needing to be carried out as usual. Therefore, online learning is a learning strategy that can be applied in times of crisis like this. Application of online learning, which is carried out without planning and suddenly makes several obstacles arise when this learning is carried out. The purpose of this study is to find out what problems arise when implementing online learning in engineering universities during a pandemic and what solutions can be applied to overcome them. This research is a systematic literature review research with keywords used, namely